Effects of Vision Umurenge Programme (VUP) Public Works Benefits on Households’ Financial Resources Allocations in Rwanda: Application of SUR Models - Munyemana, Emmanuel; K. Mung'atu, Joseph; Ruranga, Charles (CINEFORUM, 2024)
The analysis of the effects of monetary benefits from the Vision Umurenge Programme (VUP) Public Works on households' financial resource allocations in Rwanda was conducted to assess the statistical significance of this major social safety net programme in poverty reduction among poor households. Specifically, it focused on the contribution to increased aggregate expenditure, food and non-food consumption, savings, and human capital development. The analytical framework utilized data from the latest available Rwanda's Integrated Living Conditions Survey (EICV5) of 2016/17 and published in 2018, and we applied the seemingly unrelated regression model to capture the programme’s joint effects on simultaneous financial decision-making by individuals. The results demonstrate a statistically significant and positive effects of VUP Public Works benefits on households' aggregate expenditure, and food and non-food consumption. This effect is even more pronounced among extremely poor households, confirming the achievement of one of the VUP Public Works’ policy objective of providing protective support to able-bodied poor individuals in Rwanda. However, the data do not indicate any significant effect of VUP Public Works on individual savings or investment in education, and there is evidence of a significant gender divide in the impact of VUP Public Works. This analysis generates evidence on protective potential of public works programme in Rwanda, however, there is limited evidence on programme effects on local economies promotion through secondary employments, thus further studies should empirically investigate those effects.